First record of the Early Toarcian Oceanic Anoxic Event from the Southern Hemisphere, Neuquen Basin, Argentina - Al-Suwaidi, A; Angelozzi, G; Baudin, F; Damborenea, SE; Hesselbo, S; Jenkyns, H; Mancenido, M; Riccardi, A (2010)
The first record of the Early Toarcian Oceanic Anoxic Event (c. 183 Ma) from the Southern Hemisphere is described from the Neuquén Basin, Argentina, identified chemostratigraphically on the basis of a relative increase in marine organic carbon and a characteristic negative carbon-isotope excursion (δ13Corg) in bulk rock and fossil wood. The negative excursion of -6‰ in bulk organic carbon (falling to -31.3‰) crosses the boundary of the tenuicostatum-hoelderi Andean ammonite Zones, equivalent to the tenuicostatum-falciferum/serpentinum zones of Europe. These data indicate that the Early Toarcian Oceanic Anoxic Event was a global phenomenon. © 2010 Geological Society of London.